Role of Pacific preconditioning in modulating the relationship between the spring North Tropical Atlantic SST and the ensuing El Niño. (December 2022) - Chen, Sheng; Chen, Jiepeng; Wang, Xin; He, Zhuoqi; Xiao, Ziniu
Abstract: Previous literature has indicated that a spring cold sea surface temperature (SST) anomaly in the North Tropical Atlantic (NTA) could induce an ensuing El Niño event. However, observations show that this relationship is not always robust. For example, the spring cold NTA SST anomalies are not necessarily accompanied by El Niño events in the ensuing winter. Two types of cases are further classified for comparison: a spring cold NTA SST anomaly accompanied by an El Niño (tagged as NTA-El Niño) and a spring cold NTA SST anomaly accompanied by no El Niño (tagged as NTA-Normal). Statistical analysis indicates that Pacific preconditioning acts an important role in modulating the NTA SST and El Niño relationship. The zonal wind anomaly over the eastern subtropical Pacific serves as an important medium linking the spring NTA SST anomaly to the subsequent development of El Niño, and this part of the zonal wind anomaly in spring and summer is largely associated with the preceding winter tropical Pacific SST anomaly. The proposed mechanism is verified by two groups of Coupled General Circulation Models (CGCMs) runs with a weak and strong La Niña condition. Compared with the strong La Niña case, under a weak La Niña case in the previous winter, the spring cold NTA SST anomaly is more capable of modulating the development of the ensuing El Niño event. The present study suggests the importance of Pacific preconditioning while forecasting ENSO with the precursor of the spring NTA SST anomaly. Highlights: Our study shows the relationship between North Tropical Atlantic (NTA) in spring and ensuing ENSO is not always stable. Pacific preconditioning plays a key role in modulating the NTA SST and El Niño relationship. The proposed mechanism is verified by a set of Coupled General Circulation Model experiments.